(untitled) (Metakognisi, 2025)
This article discusses the educational leadership model implemented by Brigadier General TNI Syam’un and KH Mas Abdurachman, two figures who contributed significantly to the world of Indonesian education. Through different approaches, these two figures show that leadership in education can have a big impact on the character formation of the younger generation. Brigadier General TNI Syam’un puts forward a leadership model based on military discipline, nationalism and national spirit. He focuses on developing tough and patriotic individuals, creating a learning environment that emphasizes discipline and responsibility. In contrast, KH Mas Abdurachman emphasizes spiritual and moral values ​​in his leadership, with a servant leadership approach that encourages collaboration, inclusiveness and character development based on Islamic values. Even though they come from different backgrounds, these two figures agree that education is not only aimed at producing academically intelligent individuals, but also at forming good characters and making positive contributions to society. This article underlines the importance of integrating the values ​​of discipline, morals and nationalism in educational leadership models to create a generation that is ready to face challenges. This research explores the educational leadership model implemented by Brigadier General TNI Syam’un and KH Mas Abdurachman, two figures who have had a big influence in the world of education in Indonesia. Brigadier General TNI Syam’un is known for his disciplined leadership approach, prioritizing the values ​​of nationalism and responsibility. Through his firm and structured leadership model, he succeeded in forming a generation that is not only academically intelligent but also patriotic and independent. On the other hand, KH Mas Abdurachman applies a more humanistic leadership model, focusing on developing character, morals and spirituality. He prioritizes the principle of servant leadership, which encourages collaboration and active participation from all parties in the educational process. This second approach shows that effective educational leadership must be able to integrate discipline, morality and social values ​​to create a conducive learning environment. These findings underline the importance of the role of leadership in shaping the character and values ​​of the younger generation, as well as the contextual relevance of Syam’un and KH Mas Abdurachman’s leadership model. Keywords: Leadership, KH. Syam’un, KH. Mas Abdurachman, Models, and Education.